Gonadotropin-Releasing Hormone (GnRH) Receptor Structure and GnRH Binding - Flanagan, Colleen A.; Manilall, Ashmeetha (Frontiers in Endocrinology, 2017)
Gonadotropin-releasing hormone (GnRH) regulates reproduction. The human GnRH receptor lacks a cytoplasmic carboxy-terminal tail, but has amino acid sequence motifs characteristic of rhodopsin-like, class A, G protein-coupled receptors. This review will consider how recent descriptions of X-ray crystallographic structures of G protein-coupled receptors in inactive and active conformations may contribute to understanding GnRH receptor structure, mechanism of activation and ligand binding. The structures confirmed that ligands bind to variable extracellular surfaces, whereas the seven membrane-spanning α-helices convey the activation signal to the cytoplasmic receptor surface, which binds and activates heterotrimeric G proteins. Forty non-covalent interactions that bridge topologically equivalent residues in different transmembrane helices are conserved in class A G protein-coupled receptor structures, regardless of activation state. Conformation-independent interhelical contacts account for a conserved receptor protein structure and their importance in the GnRH receptor structure is supported by decreased expression of receptors with mutations of residues in the network. Many of the GnRH receptor mutations associated with congenital hypogonadotropic hypogonadism, including the Glu2.53(90) Lys mutation, involve amino acids that constitute the conserved network. Half of the ~250 intramolecular interactions in G protein-coupled receptors differ between inactive and active structures. Conformation-specific interhelical contacts depend on amino acids changing partners during activation. Conserved inactive conformation-specific contacts prevent receptor activation by stabilizing proximity of transmembrane helices 3 and 6 and a closed G protein binding site. Mutations of GnRH receptor residues involved in these interactions, such as Arg3.50(139) of the DRY/S motif or Tyr7.53(323) of the N/DPxxY motif, increase or decrease receptor expression and efficiency of receptor coupling to G protein signaling, consistent with the native residues stabilizing the inactive GnRH receptor structure. Active conformation-specific interhelical contacts stabilize an open G protein binding site. Progress in defining the GnRH binding site has recently slowed, with evidence that Tyr6.58(290) contacts Tyr5 of GnRH, whereas other residues affect recognition of Trp3 and Gly10NH2. The surprisingly consistent observations that GnRH receptor mutations that disrupt GnRH binding have less effect on “conformationally-constrained” GnRH peptides may now be explained by crystal structures of agonist-bound peptide receptors. Analysis of G protein-coupled receptor structures provides insight into GnRH receptor function.